Performance of Rainfed Farming Systems in Mahaboobnagar district of Andhra Pradesh - G.R.Desai,; J.Venkateswarlu,; S.V.Ramana Rao,; T.D.S.Kumar,; P.L.Manohari, (Journal of Agricultural Extension Management, 2025)
Andhra Pradesh is the 5th largest Indian State with a geographical area of 274.40 lakh ha. and a population of 75.7 million which is 7.37% of the country's population (2001 census). Agriculture contributes to the tune of 19% for the state GDP and provides employment to 65% of the state's population. The state enjoys a position of pre-eminence in respect of crop production